Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.20965/jdr.2014.p0858
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Analysis for Flood Risk Management in the Selected River Basins of Southeast Asia

Abstract: Flood features were analyzed and risk knowledge was examined in studies in selected river basins of Southeast Asia. Rainfall runoff features were analyzed in Indonesia’s Solo river basin and in the Philippines’ Pampanga and Cagayan river basins using ground-observed and satellite-based (GSMaP) rainfall data. Flood damage was assessed for risk management by considering physical damage to agricultural and household in the Cambodian flood plain of the Lower Mekong Basin and in the Philippines’s Pampanga river bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…The coupled assessment of flood risks and benefits across a range of return intervals can be an improved information tool to support decisions that can result in practices to reduce flood risk while meeting with potential socio‐economic preferences and environmental objectives (Juarez‐Lucas & Kibler, ). For instance, flood risk assessments in the context of the Philippines have focused on damage evaluation of agriculture and residential buildings or human affections following extreme events (Acosta et al, ; Kure, Jibiki, Iuchi, & Udo, ; Kwak & Iwami, ; Shrestha et al, ). Though evaluations of vulnerability and community adaptations to floods figure prominently (Gaillard et al, ; Lee & Vink, ; Tatlonghari & Paris, ; Uy et al, ; Zoleta‐Nantes, ), analyses of coping capacity within a probabilistic framework are infrequently addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coupled assessment of flood risks and benefits across a range of return intervals can be an improved information tool to support decisions that can result in practices to reduce flood risk while meeting with potential socio‐economic preferences and environmental objectives (Juarez‐Lucas & Kibler, ). For instance, flood risk assessments in the context of the Philippines have focused on damage evaluation of agriculture and residential buildings or human affections following extreme events (Acosta et al, ; Kure, Jibiki, Iuchi, & Udo, ; Kwak & Iwami, ; Shrestha et al, ). Though evaluations of vulnerability and community adaptations to floods figure prominently (Gaillard et al, ; Lee & Vink, ; Tatlonghari & Paris, ; Uy et al, ; Zoleta‐Nantes, ), analyses of coping capacity within a probabilistic framework are infrequently addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Damages to rice agriculture are also often reported during typhoon months (Juarez‐Lucas et al, ). While concentration time in Pampanga Basin to Candaba area is usually less than 12 hr (Shrestha et al, ), typhoon‐driven events often result in 2–3 days of heavy rainfall. We, therefore, consider hourly time steps and a simulation period of 30 days.…”
Section: Methodsmentioning
confidence: 99%
“…It is shown that the impact on crops production, mainly on rice has been the majority of those researches (Caruso et al, 285 2016;D'Arrigo et al, 2011;D'Arrigo and Wilson, 2008;Kawanishi and Mimura, 2015;Keil et al, 2009;Naylor et al, 2001;Sano et al, 2013;Shofiyati et al, 2014). This is strongly related to the examination of too much water which can cause flood Marfai et al, 2015Marfai et al, , 2014Muis et al, 2015;Neolaka, 2013Neolaka, , 2012Sarminingsih et al, 2014;Shrestha et al, 2014)or too little water which can or have caused drought in Indonesia (Aldrian and Djamil, 2008;D'Arrigo and Smerdon, 2008;D'Arrigo and Wilson, 2008;D'Arrigo et al, 2006;Keil et al, 290 2009;Keil et al, 2008). A high number of researches are also done on linking droughts (Salafsky, 1994;D'Arrigo et al, 2006;D'Arrigo and Smerdon, 2008;Shofiyati et al, 2014) and fire occurrences (Usman and Hartono, 1997;Fang and Huang, 1998;Brauer and Hisham-Hashim, 1998;Jim, 1999;Stolle and Tomich, 1999;Page et al, 2002;Stolle and Lambin, 2003) especially those on forest fire.…”
Section: Discussionmentioning
confidence: 99%
“…The next topic that receives greater attention is on the evaluation of recover and reconstruction that have taken place after the 2004 Indian Ocean 235 tsunami which hit Aceh, located in the Island of Sumatera (Chang et al, 2011;Daly and Brassard, 2011;Godavitarne et al, 2006;Guarnacci, 2012;Karan and Subbiah, 2011;Telford and Cosgrave, 2007). Within the period after 2004, other topics that are also related to the impacts of tsunami and disasters in general is the role of culture, gender, or religion in helping the community to be resilient in facing disasters, and also how various disasters in Indonesia have impacted various community groups differently in relation to their culture or gender (Baumann, 2008;Donovan, 2010;Donovan et al, 2012;Gaillard et al, 240 2008b;Islam and Lim, 2015;Balgos et al, 2012;Guarnacci and Di Girolamo, 2012;Hiwasaki et al, 2015;Siagian et al, 2014;Sagala et al, 2009). …”
Section: Disaster Risk Reduction 220mentioning
confidence: 99%
“…It is shown that the impact on crops production, mainly on rice has been the majority of those researches (Caruso et al, 2016;D'Arrigo et al, 2011;D'Arrigo and Wilson, 2008;Kawanishi and Mimura, 2015;Keil et al, 2009;Naylor et al, 2001;Sano et al, 2013;Shofiyati et al, 2014). This is strongly related to the examination of too much water which can cause flood (Marfai and King, 2008a;Marfai et al, 2008;Marfai et al, 2014Marfai et al, , 2015Muis et al, 2015;Neolaka, 2012Neolaka, , 2013Sarminingsih et al, 2014;Shrestha et al, 2014)or too little water 345 which can or have caused drought in Indonesia (Aldrian and Djamil, 2008;D'Arrigo and Smerdon, 2008;D'Arrigo and Wilson, 2008;D'Arrigo et al, 2006;Keil et al, 2009;Keil et al, 2008). A high number of researches are also done on linking droughts (D'Arrigo and Smerdon, 2008;D'Arrigo et al, 2006;Salafsky, 1994;Shofiyati et al, 2014) and fire (Brauer and Hisham-Hashim, 1998;Fang and Huang, 1998;Jim, 1999;Page et al, 2002;Stolle and Lambin, 2003;Stolle and Tomich, 1999;Usman and Hartono, 1997) occurrences especially those on forest fire.…”
mentioning
confidence: 99%